THE METHOD OF PROBLEMS VERSUS THE METHOD OF TOPICS - Fred Eidlin (Сравнительная политика, 2015)
Many scholars face a difficulty in formulating a research problem and research question while working on the research. The author introduces several methods that would help researchers to be more precise while working on the architecture of their research topic.